Automotive Breakthroughs: Navigating Towards A Sustainable Future - Samadov Muhiddin Akhadovich (Genius Journals, 2024)
Automotive engineering is at the forefront of driving advances in technological innovation, vehicle design, propulsion systems, safety features, and sustainability initiatives. This research paper explores the dynamic landscape of the automotive industry, highlighting key developments in electric vehicles, autonomous driving technologies, lightweight materials and environmentally friendly power plants. By examining current trends and future prospects in the field, this study highlights the critical role of the automotive industry in shaping the future of transportation into a more sustainable and efficient paradigm
Keywords: Automotive; electric vehicles; autonomous driving; sustainable mobility